Impaired Sacculocollic Reflex in Lateral Medullary Infarction - Kim, Seonhye; Kim, Hyo-Jung; Kim, Ji Soo (Frontiers in Neurology, 2011)
Objective: The aim of this study was to determine saccular dysfunction by measuring cervical vestibular-evoked myogenic potentials (cVEMP) and to correlate abnormality of cVEMP with results of other vestibular function tests in lateral medullary infarction (LMI). Methods: We recorded cVEMP in 21 patients with LMI documented on MRI. cVEMP was induced by a short tone burst and was recorded in contracting sternocleidomastoid muscle while patients turned their heads forcefully to the contralateral side against resistance. Patients also underwent video-oculographic recording of spontaneous, gaze-evoked and head shaking nystagmus (HSN), evaluation of ocular tilt reaction (OTR), measurement of the subjective visual vertical (SVV) tilt, bithermal caloric tests, and audiometry. Results: Nine patients (43%) showed abnormal cVEMP, unilateral in seven and bilateral in two. The cVEMP abnormalities included decreased p13–n23 amplitude in four, delayed p13/n23 responses in five, and both decreased and delayed responses in two. The abnormal cVEMP was ipsilesional in five, contralesional in two, and bilateral in two. The prevalence of OTR/SVV tilt, spontaneous nystagmus, and HSN did not differ between the patients with normal and abnormal cVEMP. Conclusion: cVEMP was abnormal in approximately half of the patients with LMI. The abnormal cVEMP indicates damage to the descending sacculocollic reflex pathway or disruption of commissural modulation between the vestibular nuclei.